(untitled) (International Journal of Engineering and Computer Science, 2014)
In present work Silver nonoparaticles have been prepared by using pulsed laser ablation ( Q -switched Nd:YAG) 1064nm pluse duration and(E= 100mJ to 400mJ ) of pure Ag mateal plate immersed in distilled water and dionized water .The synthesized nanoparticles are characterized using transmittance electron microscopy (TEM) and UV-VIS spectrophotometer . The effect of the pulses energies and number. of shots have been reported .The silver nanoparticles exhibited asurface Plasmon resonance effect with wave length (λspr=400nm).The production of pure and spherical Ag with average size of (1-15nm) .All the size measurements have been confirmed by TEM.